Enhanced iturin a production in a two-compartment biofilm reactor by Bacillus velezensis ND - Tang, Zhongmin; Zhang, Huili; Xiong, Jie; Li, Yang; Luo, Wei (Frontiers in Bioengineering and Biotechnology, 2023)
In this study, a two-compartment biofilm reactor was designed for iturin A production. The biofilm reactor consists of a stirred-tank fermentor containing exclusively suspended cells and a packing column where the biofilm is attached. Polyester fiber with sphere shape and rough surfaces was chosen as the carrier of biofilm in packing column. Batch, fed-batch, and repeated-batch fermentation using Bacillus velezensis ND in the biofilm reactor were studied. Compared to conventional suspended cell fermentations, the productivity of iturin A in batch and fed-batch biofilm fermentation were increased by 66.74% and 63.27%, respectively. Maximum itutin A concentration of 6.76±0.09 g/L and productivity of 46.94±0.23 mg/L/h were obtained in fed-batch biofilm fermentation. Repeated-batch fermentation showed high stability, with almost same profile as batch fermentation. After a step-wise temperature control strategy was introduced in the biofilm reactor, productivity of iturin A was increased by 131.91% than suspended cell reactor. This superior performance of biofilm reactor confirms that it has great potential in industrial production of iturin A.